Colour, it's just a constant problem': an examination of practice, infrastructure and workflow in colour printing - Martin, David; O'Neill, Jacki; Colombino, Tommaso; Roulland, Frederic; Willamowski, Jutta (Computer Supported Cooperative Work, 2010)
Two interrelated topics that have been of enduring interest to researchers in studying cooperative work practices and the design and use of technologies to support those practices are workflow and, to a slightly lesser extent, infrastructure. Workflow systems are a classic form of technology employed to coordinate cooperative work along a process of production where different workers (potentially in different companies and locations) complete different tasks along a ‘line’ of production. The workflow and the technologies that embody or enforce it are designed to maintain adherence to procedure and coordination across time and place. The central issues surrounding the treatment of workflow in Computer Supported Cooperative Work (CSCW) and related disciplines have been the problem of getting workflow systems to mesh with the particularities of local flows of work among people. Since Suchman (1983, 1987), at least, there has been a presiding concern with the ways in which workflow models fail to take into account the local, embodied, non-prescriptive and emergent manner (responding to dynamic local circumstances) in which people organise their work. Workflow systems have been criticised for being designed from ‘elsewhere’ – with an inadequate, overly idealistic or abstracted understanding of the work they are meant to assist. People end up having to organise or translate (potentially after-the-fact) their work, so it fits with the workflow system or workaround or ignore the technology completely (see Bowers et al. 1995) for an example from the print industry).